STATUS KEPEMILIKAN KENDARAAN YANG DIBELI TANPA BALIK NAMA DALAM JUAL BELI KENDARAAN BERMOTOR BEKAS PAKAI DI SAMARINDA - Mohammad Alexander Wahyudi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTImplementation of the sale and purchase of used vehicles, which exist in the society is soft enough in terms of payment.There are two ways / options given to prospective buyers, namely: in installments and in cash. Sale and purchase is also equipped with supporting evidence proof of ownership of used vehicles, such as vehicle registration and reg, which is of course the name of the original owner still attached to mail the letter.If the original owner to report to the competent authority, in this case SAMSAT, that the vehicle in her name have been sold, the new owner or purchaser must immediately resolve the new ownership papers.However, this condition to the parties who make buying and selling. This is consistent with the intent of the content of article 1338 of the Civil Code of the principle of freedom of contract, that everyone is given the possibility to make an agreement, which is valid as a law for them, as long as the agreement was not contrary to the provisions of existing law.